School-Community Practices in the Implementation of Brigada Eskwela in Public Elementary Schools - Pines, Joseph (International Journal of Sustainability and Advanced Integrated Research, 2025)
This study examined school–community practices in the implementation of Brigada Eskwela in selected public elementary schools in one division in Albay. It explored how organizing, leading, resource mobilization, and collaboration contribute effective school readiness, guided by principles of volunteerism and community participation. A descriptive research design was used, and validated questionnaires were administered to 110 respondents comprising school heads and teachers. Data were analyzed using  frequency counts, percentages, weighted means, chi-square tests, and ANOVA. Finding showed that organizing and leading practices were implemented to a very high extent, supported by systematic planning, needs assessment, communication, and leadership. Resource mobilization was much practiced, while community and school collaboration were only moderately practiced, as stakeholder engagement was concentrated mainly during the Brigada Eskwela period. Readiness levels followed the same trend, with high readiness in organizing and leading but weaker readiness in collaborative dimensions. ANOVA revealed significant differences across dimensions, indicating uneven program implementation. The study highlights the need for year-round stakeholder engagement, stronger volunteer coordination, and enhanced communication systems. It aligns with SDG 4, SDG 11, and SDG 17 by emphasizing shared responsibility for safe, inclusive, and prepared learning environments. Overall, the finding demonstrate how structured school-community partnerships contribute to the sustainability of educational institutions.
Keywords: Brigada Eskwela; Community Collaboration; Functional Theory of Volunteerism; Public Elementary Schools; Resource Mobilization; School–Community Partnership; Sustainable Development Goals; Volunteerism